Sex differences in HIV-associated cognitive impairment. (28th November 2018) - Sundermann, Erin E.; Heaton, Robert K.; Pasipanodya, Elizabeth; Moore, Raeanne C.; Paolillo, Emily W.; Rubin, Leah H.; Ellis, Ronald; Moore, David J.
Abstract : Objective: We determined whether there are sex differences in the prevalence and profile of HIV-associated neurocognitive impairment, and whether sex moderates the effect of HIV-serostatus on neurocognitive impairment among HIV-positive and HIV-negative individuals. Secondarily, we assessed whether differences were explained by greater biopsychosocial risk factors in HIV-positive women. Design: An observational cohort study. Methods: Analyses included 1361 HIV-positive (204 women) and 702 HIV-negative (214 women) (ages = 18–79 years) participants from the UCSD HIV Neurobehavioral Research Program. Demographically corrected standardized T -scores from 15 neuropsychological tests were used to calculate domain-specific and global deficit scores (GDS). GDS at least 0.5 defined neurocognitive impairment. Biopsychosocial risk factors included low education, low reading level (education quality), lifetime substance use disorders, depressed mood (clinically significant depressive symptoms and/or current major depressive disorder) and a cumulative syndemic count (sum of biopsychosocial risk factors, range = 0–4). Race-stratified analyses were conducted. Analyses were adjusted for relevant demographic and clinical factors. Results: HIV-associated neurocognitive impairment was more prevalent in women versus men; however, the difference was eliminated after adjustment for reading level. In sex-stratified logistic regressions, the association between HIV-seropositivity and higher likelihood of neurocognitive impairment was stronger in women versus men; however, the association was attenuated in women, but not men, after adjusting for reading level. These results in the overall sample were specific to blacks. Sex differences in the profile of HIV-associated neurocognitive impairment varied by race. Conclusion: Women, particularly black women, were most at-risk for HIV-associated neurocognitive impairment. Higher rates of HIV-associated neurocognitive impairment in women versus men may reflect differences in educational quality. Abstract : Supplemental Digital Content is available in the text